SINTESIS ZEOLIT DENGAN KANDUNGAN Si/Al RENDAH DARI KAOLIN MENGGUNAKAN METODE PELEBURAN DAN HIDROTERMAL - Setiadi, Amir (Universitas Negeri Semarang, 2016)
Kaolin contains silicon 42,3% and aluminium 24% therefore it is potential as basic material for zeolite synthesis process. Zeolite can be synthesized from material which contains Si and Al. In this study it synthesized zeolite from kaolin using fusion and hidrotermal method. Kaolin was mixed with NaOH powder as mineralizer. Fusion method was carried out on temperature of 450Â°C for 2 hours then followed by hidrothermal method which was carried out on 175Â°C for 6 hours. Pro analyst NaOH and technical NaOH were used in this research. This aimed to distinguish the synthesized zeolites from two types of NaOH. The mixing of NaOH powder/kaolin (w/w) is variated respectively 0,5; 1; 1,25; and 1,5. Characterizations of synthesized zeolite were performed by using XRD, FTIR, and SEM. Characterization result showed that zeolite with technical NaOH/kaolin ratio=1,25 producing percentage of zeolite A (LTA) relative intensity 37,54% and percentage of crystallinity 91,42%. Zeolite with pro analyst NaOH/kaolin ratio=1 producing percentage of zeolite A (LTA) relative intensity 22,72% and percentage of crystallinity 85,37%. This research showed that based on qualitative aspect, pro analyst NaOH is better as mineralizer in synthesize of zeolite A signed by more peaks, while based on quantitative aspect, technical NaOH is better as mineralizer signed by high crystallinity and pecentage relative intensity value.